Audit on the quality of discharge summary in TU Teaching Hospital - Pradhananga, Rb; Gurangain, RPS (Journal of Institute of Medicine Nepal, 2007)
Background: To find out whether all the criteria of discharge summary outlined in modified Van- Walraven et al. 1999, were met in the discharge summary. To determine the completeness of the discharge summary form printed by the hospital Methods: Review of the records of 20 discharge summary form from each seven departments of Tribhuvan University Teaching Hospital (TUTH) between April 2005 and September 2005. The notes were looked for completeness and inclusion of all criteria outlined in modified van Walraven et al 1999. Results: According to van Walraven et al Modified Criteria Department of Gynaecology showed the best summaries in which most of the necessary informations were included where as Department of Orthopedics had the least inclusion of criteria. Department of ENT & Head and Neck Surgery tops the list for completeness of the hospital printed discharge form. Department of Orthopedics, again, was found to be at the bottom of the least. Conclusion: Discharge summary should be filled up completely, clearly and without missing necessary informations. Regular audit should be performed to ensure that the quality of discharge summary is maintained. Key Words: Discharge summary, van Walraven criteria. The full text of this paper is available at Journal of Institute of Medicine website